2019
DOI: 10.1002/jcp.28016
|View full text |Cite
|
Sign up to set email alerts
|

Novel cellular mechanism that mediates the collecting duct formation during postnatal renal development

Abstract: We have previously demonstrated that kidney embryonic structures are present in rats, and are still developing until postnatal Day 20. Consequently, at postnatal Day 10, the rat renal papilla contains newly formed collecting duct (CD) cells and others in a more mature stage. Performing primary cultures, combined with immunocytochemical and time‐lapse analysis, we investigate the cellular mechanisms that mediate the postnatal CD formation. CD cells acquired a greater degree of differentiation, as we observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a recent study performed with time‐lapse microscopy, we demonstrated that a very active MET occurs in the postnatal development of renal CD, where mesenchymal cells migrate and insert into the tubules being formed and after insertion, the cells undergo effective MET (Guaytima et al,2019). Thereafter, we also reported that in the mature kidney, there is a balance between the CD cells that carry out EMT and those that carry out MET, thus maintaining tissue homeostasis.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In a recent study performed with time‐lapse microscopy, we demonstrated that a very active MET occurs in the postnatal development of renal CD, where mesenchymal cells migrate and insert into the tubules being formed and after insertion, the cells undergo effective MET (Guaytima et al,2019). Thereafter, we also reported that in the mature kidney, there is a balance between the CD cells that carry out EMT and those that carry out MET, thus maintaining tissue homeostasis.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we showed that cultured renal papillary CD cells from young rats expressed the epithelial cell marker cytokeratin 7, whereas only some cells expressed VIM, and few CD cells lightly expressed α ‐SMA, resembling the epithelial phenotype of CD cells (Brandán et al,2018). On the other hand, overlapping cells with high expression of α ‐SMA and with mesenchymal phenotype, first insert into the colony, adhere to other cells, and then they progressively lose the mesenchymal markers and acquire the epithelial ones (Guaytima et al,2019). In the present study, we found that during renal aging, CD cells undergo several steps of EMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation